The North East after Brexit : impact and policy - Liddle, Joyce; Shutt, John (Bingley, U.K. : Emerald Publishing Limited, 2019)
The North East is one of Britain's most disadvantaged regions. This area, where wealth was generated from coal, steel and engineering during the Industrial Revolution, has struggled to progress at the same rate as regions in Southern England. With a reliance on public sector services, the North East is set to be one of the hardest hit areas after Britain's exit from the European Union. The North East after Brexit arises from new research and activities at Northumbria University to shape the future of public sector management in the region. Across a range of new themes and governance, work is focused on how public sector agencies can work better together to shape the Northern economy in the future. The North East is a key partner in the Northern Powerhouse involving three northern regions and is designed to rebalance the northern economy in the UK and bridge the chasm between north and south. This important text is set within the context of the Northern Powerhouse; a highly complex and challenging concept that demands the development of new partnerships across the regions, and the need for collaborative working across city regions in the north. With a focus on Brexit and austerity as key drivers of change, this invaluable text contributes to debates in the region surrounding employment changes and policy directions in a post- Brexit world. It will prove to be an essential read for policy makers, government researchers and those working in the fields of public sector leadership and management. Joyce Liddle is a Professor of Public Leadership and Enterprise, Director of Research and Innovation and John Shutt is a Professor of Public Policy and Management. Both are located at Newcastle Business School, Northumbria University, UK.
Part I The impacts of devolution on the North East -- Chapter 1. An underpowered Northern powerhouse: infrastructure in the ungovernable North / Nicola Headlam -- Chapter 2. Combined authorities and governance in the Northern powerhouse: critical issues and what next? / Joyce Liddle and John Shutt -- Chapter 3. The NHS plan and the importance to the North East region / Debbie Porteous -- Part II The impacts of Brexit and key policy areas -- Chapter 4. Developing a post-Brexit economy: challenges for the North East of England / Ignazio Cabras -- Chapter 5. Industrial strategies and the North: will an industrial strategy and a new local industrial strategy deliver something new? / David Charles -- Chapter 6. Brexit and devolution: a view from 'North of the Tyne' and the Anglo-Scottish borderlands / Keith Shaw -- Chapter 7. The North East as a tourism destination: a hidden gem? / Tom Mordue -- Chapter 8. Small firms and innovation in North East: can we create more dynamism? / Michele Rusk -- Part III The public sector and next steps after Brexit -- Chapter 9. Whose business growth is it anyway?: co-producing a new approach to business support for the North / Rob Wilson -- Chapter 10. Developing public sector entrepreneurship in the universities: accelerating innovation in the North / James Cunningham -- Chapter 11. Research knowledge and exchange and impact: the experience of a university partnership in North East England / John Mawson and Martyn Griffin Chapter -- 12. The future of public administration, teaching and research in the North East / Lorraine Johnstone and Ian Elliott -- Chapter 13. Developing a focus on future research for the region / Joyce Liddle and John Shutt -- Bibliography -- Index.
Includes bibliographical references and index.
Print version record.
Keywords: Public administration -- England; European Union -- Great Britain; Political Science -- Public Affairs & Administration; Public administration